A taxonomic revision of the profusella species group of the genus Nemophora Hoffmannsegg (Lepidoptera, Adelidae) from Sulawesi, Papua and adjacent islands - Kozlov, Mikhail V. (Zootaxa, 2026)
This study provides a comprehensive account of 20 species of the genus Nemophora Hoffmannsegg, 1798, described or recorded from Indonesia (15 species) and Papua New Guinea (8 species). These species presumably constitute a monophyletic group defined by the presence of two longitudinal silver stripes in light (yellow, ochreous, or golden) basal part of forewing. A key to the species is provided; 12 new species are described: N. baliella Kozlov, sp. nov., N. cheesmanae Kozlov, sp. nov., N. cupriantennella Kozlov, sp. nov., N. fuscofasciella Kozlov, sp. nov., N. illustrella Kozlov, sp. nov., N. meeki Kozlov, sp. nov., N. neuguineae Kozlov, sp. nov., N. ochrodorsella Kozlov, sp. nov., N. sulawesiensis Kozlov, sp. nov., N. sulphurea Kozlov, sp. nov., N. vasilyi Kozlov, sp. nov., and N. wallacei Kozlov, sp. nov. Lectotypes are designated for two species, Nemotois profusella Walker, 1866 and Nemotois photodoxa Meyrick, 1930.